2020
DOI: 10.1088/1755-1315/492/1/012112
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of heritability value and non genetic factor affecting reproduction traits in Ongole cross cattle

Abstract: Evaluation of genetic factors such as heritability value and non genetic factors of reproductive traits has a vital role in improving breeding and management practices of beef cattle. The aim of the present study was to evaluate heritability value and non-genetic factors affecting reproductive traits in Ongole grade cattle. Five hundred and fifty-three (553) records of reproductive traits including age at first calving (AFC), calving interval (CI), days open (DO) of cows distributed over a period of 8 years (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Gunawan et al. (2020) reported that AFC, CI and DO were non‐significantly ( p > .05) affected by parity and year of birth whereas AFC showed significant association with season of calving. Gunawan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gunawan et al. (2020) reported that AFC, CI and DO were non‐significantly ( p > .05) affected by parity and year of birth whereas AFC showed significant association with season of calving. Gunawan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dev et al (2021) reported that period of calving had statistically significant effect (p < .05) on all production performance traits except on AFC, SP, CI and DP whereas season of calving had non-significant effect on all the production performance traits except significant effect on AFC, SP, CI and DP and the effect of parity was found to be statistically significant (p < .01, p < .05) on all the traits except on LL, PY, SP and CI. Gunawan et al (2020) reported that AFC, CI and DO were non-significantly (p > .05) affected by parity and year of birth whereas AFC showed significant association with season of calving.…”
Section: Phenotypic Correlations Among Traitsmentioning
confidence: 95%
“…Ongole Grade (OG) cattle known as "Sapi PO" is one of the prominent Indonesian cattle breeds. This breed of cattle is originated from crossing between Sumba Ongole cattle (originated from India) and Javanese cattle (Bos javanicus) and is adapted to tropical environments in Indonesia since a hundred years ago [1,2]. The cattle which is predominant breed especially in Java Island and also it spreads in many island in Indonesia, reared primarily for meat production.…”
Section: Introductionmentioning
confidence: 99%